PENERAPAN ZERO WASTE FASHION PADA BUSANA DEMI COUTURE DENGAN TEKNIK SASHIKO - Vidya Kartika Dewi (Moda : The Fashion Journal, 2022)
In the process of making a fashion product, especially clothes, it is known that at the end of the production process there is waste produced in the form of cloth. To reduce fabric waste generated in the production process, there is potential to apply the zero-waste fashion design method. Zero-waste fashion design is a method of reducing waste in the fashion production process. The zero-waste fashion design method maximizes the use of fabric dimensions in the fashion-making process by adjusting the pattern of clothing used to produce less than 15% waste. This study aims to apply the zero-waste fashion design method to demi-couture clothing collection. As an added attraction, the clothing produced in this study uses the application of the Sashiko technique as a decorative element. The research method that being used is a qualitative research method with data collection techniques in the form of literature study, observation, and exploration. The result of this research is in the form of a demi-couture clothing collection with the application of the zero-waste fashion design method into the clothing collection. Keywords: zero waste fashion design; demi-couture; sashiko.